Olive oil and health [ - Quiles, Jose L.; Ramirez-Tortosa, M. Carmen (CABI, 2006)
Discussions on the various health promoting and disease preventing properties of olive oils and its components are presented, with focus on cardiovascular diseases, neoplasms and diabetes and other metabolic disorders. Also, chapters on the chemical comosition and physicochemical properties of olive oils, including the various methods used to analyse them, are presented.